Alcohol and other substance use among medical and law students at a UK university: a cross-sectional questionnaire survey. Issue 1109 (4th November 2017) - Bogowicz, Paul; Ferguson, Jennifer; Gilvarry, Eilish; Kamali, Farhad; Kaner, Eileen; Newbury-Birch, Dorothy
Abstract: Purpose of the study: To examine the use of alcohol and other substances among medical and law students at a UK university. Study design: Anonymous cross-sectional questionnaire survey of first, second and final year medical and law students at a single UK university. Results: 1242 of 1577 (78.8%) eligible students completed the questionnaire. Over half of first and second year medical students (first year 53.1%, second year 59.7%, final year 35.9%) had an Alcohol Use Disorders Identification Test (AUDIT) score suggestive of an alcohol use disorder (AUDIT≥8), compared with over two-thirds of first and second year law students (first year 67.2%, second year 69.5%, final year 47.3%). Approximately one-quarter of medical students (first year 26.4%, second year 28.4%, final year 23.7%) and over one-third of first and second year law students (first year 39.1%, second year 42.4%, final year 18.9%) reported other substance use within the past year. Over one-third of medical students (first year 34.4%, second year 35.6%, final year 46.3%) and approximately half or more of law students (first year 47.2%, second year 52.7%, final year 59.5%) had a Hospital Anxiety and Depression Scale anxiety score suggestive of a possible anxiety disorder. Conclusions: Study participants had high levels of substance misuse and anxiety. Some students' fitness to practice may be impaired as a result of their substance misuse or symptoms of psychological distress. Further efforts are needed to reduce substance misuse and to improve the mental well-being of students.